PDA-modified sol-gel coating for long-lasting corrosion protection on Al alloy 3003 - Zhiyuan Feng; Jiao Li; Keqi Huang; Guoqiang Liu; Huanhuan Bai; Xin Huang; Jun Qi; Zhengwei Tang; Penghai Xu; Xiaofei Yang; Zheng Qu; Guozhe Meng (Corrosion Communications)
Within the realm of corrosion protection methods for Al alloys, sol-gel technique has garnered increasing attention. However, conventional sol-gel methodologies cannot provide adequate long-lasting corrosion protection to Al alloys when exposed to chloride-rich solutions. This paper introduces an innovative approach to substantially augment the corrosion resistance of aluminum alloys through utilization of polydopamine (PDA)-modified sol-gel films. Effort was made to fabricate a PDA-modified sol-gel coating and a systematic investigation was conducted thereof. Long-term corrosion performance of this coating in 3.5 wt.% NaCl solution was evaluated through electrochemical impedance spectroscopy (EIS). Results show that the low-frequency impedance of the PDA-modified sol-gel coating remains significantly high at 7.9 × 105 Ω·cm2, even after 36 d of immersion in 3.5 wt.% NaCl medium, indicative of excellent protective properties. It notably surpasses low-frequency impedance of the unmodified coating, which registers at 2.5 × 104 Ω·cm2. The incorporation of PDA into the sol-gel coating, facilitated by adsorption and diffusion mechanisms, serves to fill micrometer- and nanometer-scale defects of the coating, thereby markedly enhancing their compactness. Furthermore, despite its modest thickness of 9 μm, the PDA-modified coating exhibits enduring corrosion protection capabilities.